Laboratory hoods - Sanger, John M.; The MARCOM Group, Ltd. (Boothwyn, Pa. : The MARCOM Group, Ltd., 1993)
This program explains on why laboratory hoods are needed, protections afforded by hoods, how hoods function mechanically and the proper use of laboratory hoods
Title from title screen
Executive producer, Donald L. Leonard
Keywords: Laboratories -- Safety measures; Laboratories -- Accidents -- Prevention